Attentional set protects visual marking from visual transients. Issue 1 (January 2013) - Osugi, Takayuki; Kawahara, Jun I.
When some distractors (old items) appear before others (new items) in an inefficient visual search task, the old items are excluded from the search (visual marking). Previous studies have shown that changing the shape of old items eliminates this effect, suggesting that shape identity must be maintained for successful visual marking. However, the contribution of top-down target knowledge to the maintenance of visual marking under shape change conditions has not been systematically examined. The present study tested whether the vulnerability of visual marking to shape change is contingent on observers' attentional set, by manipulating compatibility of the set and the domains in which the change occurs. The results indicated that visual marking survived shape changes when the observer's attentional set was consistent with critical features between the old and new items. This protection was observed when the set was based on explicit instructions at the beginning of the experiment, and when the task set was implicitly carried over from the previous task. These results suggest that top-down processes play a role in maintaining memory templates by enhancing the grouping and suppression processes during visual search, despite disruptive bottom-up signals.